Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan Consumer Goods - Pramukti, Andika; Pelu, Muh Faisal AR; Kalsum, Ummu; Bakri, Arsi Ady (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The purpose of this study was to examine the effect of implementing of Good Corporate Governance on financial performance. The entire research population was Consumer Goods companies listed on the Indonesia Stock Exchange in 2018-2020. Based on the result of the purposive sampling method, 17 companies have been selected as sample. The analysis instruments are partial regression. The results of the test is indicates that managerial ownership, board of independent commissioner, and audit committee has positive significant influence to the financial performance. Partially institutional ownership negatively significant affect to the financial performance.